2011
DOI: 10.4028/www.scientific.net/amr.311-313.1551
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Coexistence of Porous Ecological Concrete with Plants

Abstract: The effects of mix proportions on the properties of porous ecological concrete, and its coexistence with plants are discussed in this paper. In conclusion, the strength of porous ecological concrete is governed simultaneously by water cement ratio and cement content. Permeability is increased with any increment in aggregate gradation and any decrease in cement paste content. The thicknesses of concrete blocks and topsoil affect the growth of plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…By varying the amount of ACB powder and SCG ash with a fixed water–binder ratio of 0.3, the impact of these materials on the green-growing concrete’s porosity was investigated [ 38 , 39 ]. The specific test results are shown.…”
Section: Test Results and Analysismentioning
confidence: 99%
“…By varying the amount of ACB powder and SCG ash with a fixed water–binder ratio of 0.3, the impact of these materials on the green-growing concrete’s porosity was investigated [ 38 , 39 ]. The specific test results are shown.…”
Section: Test Results and Analysismentioning
confidence: 99%
“…Porous concrete (POC) is a new type of concrete material with a continuous porous structure, which is composed of coarse aggregate or a small amount of fine aggregate, cementing material and water. Its internal porosity can reach 20%~30%, with good air and water permeability, which can adapt to plant growth and increase the environmental benefits of the project [ 18 , 19 , 20 ]. However, the unique porous structure also limits the overall mechanical properties, causing this material to be mainly used in low-strength engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have carried out an impact analysis of the components and mix ratio, the basic mechanical properties, and void and alkaline testing of grass-planting concrete [4][5][6][7]. It has been found that the strength viability of porous concrete depends not only on the void, but also on the size of the coarse aggregate and the water-cement ratio [8][9][10]. To meet void requirements, the strength of concrete may be reduced by using less mortar [11], and other materials such as limestone powder, ganister powder, and fly ash are used to replace cement and achieve high compressive and tensile strength of the concrete [12][13][14].…”
Section: Introductionmentioning
confidence: 99%